2002
DOI: 10.1177/156482650202300420
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Undernutrition in Rural Ethiopia: Magnitude, Correlates, and Functional Significance

Abstract: 427Consecuencias de la desnutrición en el escolar peruano. Ernesto Pollitt. Pontificia Universidad Catolica del Peru, Lima, Peru, 2001. (ISBN 9972-42-452-9) 417 pages, paperback.The author of this book, Ernesto Pollitt, has contributed more than any single person to our understanding of the relations among nutrition, cognition, and school performance. The book is comprehensive, authoritative, clearly written, well illustrated, and carefully documented. It reviews the factors that determine the effectiveness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…Previous studies on the association between food seasonality and the nutritional status of adults and children have reported inconsistent findings. In a study conducted in Ethiopia, children registered better WHZ scores in a period before harvest compared with a period after harvest, while the pattern observed for adults was as expecteda higher average BMI was reported in the season of plenty and a lower average BMI in the lean season (Ferro-Luzzi et al, 2002). On the other hand, a Kenyan study did not find significant seasonal differences in children's mean weight changes, but the percentage of children stunted was higher during the lean season (51%) compared with the post-harvest months (28%) (Kigutha et al, 1995).…”
supporting
confidence: 58%
“…Previous studies on the association between food seasonality and the nutritional status of adults and children have reported inconsistent findings. In a study conducted in Ethiopia, children registered better WHZ scores in a period before harvest compared with a period after harvest, while the pattern observed for adults was as expecteda higher average BMI was reported in the season of plenty and a lower average BMI in the lean season (Ferro-Luzzi et al, 2002). On the other hand, a Kenyan study did not find significant seasonal differences in children's mean weight changes, but the percentage of children stunted was higher during the lean season (51%) compared with the post-harvest months (28%) (Kigutha et al, 1995).…”
supporting
confidence: 58%
“…It is therefore possible that although during the wet season there is less maize (the staple food) and other agricultural produce, the abundance of fruits and vegetables rich in vitamin A and C that naturally grow with the rains could be supporting the nutritional needs of children in Malawi and contributing to the relatively better nutritional status of children during this season. Other studies on seasonality of child nutritional status have shown that busy harvesting times could result in reduced child care (Huffman et al, 1980) which may impact on a child's nutritional status (Mebrahtu et al, 1995) and that seasonal child nutritional status may follow a pattern of seasonal child morbidity and not necessarily seasonal food availability (Ferro-Luzzi et al, 2001;Panter-Brick, 1997;Rowland et al, 1977).…”
Section: Discussionmentioning
confidence: 97%
“…Barley, teff, enset, wheat, vegetables, pulses, and maize are the main crops grown in order of economic importance. The "false banana" enset (Ensete ventricosum) is important as an energy source to smooth out consumption fluctuations (Ferro-Luzzi et al, 2001). Teff serves both as a subsistence and cash crop.…”
Section: Income Levels and Sourcesmentioning
confidence: 99%